2018
DOI: 10.2147/dmso.s161540
|View full text |Cite
|
Sign up to set email alerts
|

The influences of bariatric surgery on hemoglobin A1c in a sample of obese patients in Saudi Arabia

Abstract: BackgroundAlthough the frequency of surgical weight loss interventions has increased in Saudi Arabia, literature describing the clinical outcomes of bariatric surgery in Saudi Arabia is limited. This study aimed to assess whether weight loss intervention improves hemoglobin A1c (HbA1c) in obese patients and to identify its associated factors.Patients and methodsA retrospective study was carried out on 318 patients with obesity class 1 or higher (body mass index [BMI] ≥ 30 kg/m2) who underwent laparoscopic slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…Previous literature reported a substantial reduction of BMI associated with HbA1c reduction within 12 months, and we noted similar results, but within 10 months [ 23 , 25 , 26 ]. Lee et al (2009) found remission of diabetes in poorly controlled patients with a 22.8% reduction in HbA1c after LSG.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous literature reported a substantial reduction of BMI associated with HbA1c reduction within 12 months, and we noted similar results, but within 10 months [ 23 , 25 , 26 ]. Lee et al (2009) found remission of diabetes in poorly controlled patients with a 22.8% reduction in HbA1c after LSG.…”
Section: Discussionsupporting
confidence: 87%
“…This effect is related to decreased insulin resistance due to calorie restriction [ 27 ]. A study done by Ahmed et al (2018) reported that patients with BMI >40 kg/m 2 had a significant reduction in weight within 12 months after LSG, with a 25% reduction of weight postoperatively [ 23 ]. Also, Ahmed et al (2018) and Sucandy et al (2013) reported a significant postoperative reduction of BMI and improved glycemic control at one year following LSG [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bariatric surgery results in a greater and more durable weight loss than the best available nonsurgical interventions for obesity, regardless of the type of bariatric procedures used [6]. Beyond weight loss, the effect of bariatric surgery extends to enhancing glycemic control [7,8], improving lipid profile [9], controlling elevated blood pressure [10], achieving type 2 diabetes mellitus remission and metabolic syndrome resolution [11,12], alleviating obstructive sleep apnea [13], augmenting renal functions [14], treating nonalcoholic fatty liver disease [15], improving quality of life and body image [16], improving fertility and sexual health [17,18], lowering cardiovascular events [19], decreasing cancer risks [20], prolonging long-term survival [19], and decreasing medical cost [21].…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective study in Saudi Arabia was carried out on 318 obese patients who underwent either LSG or RYGB, 58 of whom were diabetic. This study aimed to measure the percentage of HbA1c reduction after bariatric surgery on the two groups; the authors found that the target of HbA1c 6.5% or less was observed in 62.5% of diabetic patients and 97.1% of the non-diabetic patients [ 12 ]. Another study was done in Saudi Arabia on 56 morbidly obese patients with T2DM; a follow-up of 30 months after LSG showed a resolution of diabetes in 22%, 54%, and 90% in the third, sixth, and 12th months postoperatively, respectively [ 13 ].…”
Section: Introductionmentioning
confidence: 99%